Exploring the increase of receptive vocabulary knowledge in the foreign language: A longitudinal study - Terrazas Gallego, Melania; Agustín Llach, María del Pilar (International Journal of English Studies, 2009)
This paper tracks the increase in the overall word reception knowledge of 224 young pupils in their 4th, 5th and 6th grades of primary education and in their 1st year of secondary education 7th grade), who learn EFL in a formal context. The 2,000 word frequency band of The Vocabulary Levels Test (Schmitt, Schmitt and Clapham, 2001, version 2) is used to establish their word knowledge level. Results reveal that the development of these students’ receptive English vocabulary size is incremental and constant, and that it falls within the 1,000 frequency level. Learners increase their receptive vocabulary knowledge in a significant way from one grade to the next. The rate of the gain remains constant across grades.